Platelet-rich Plasma in the Management of Shoulder Disorders: Basic Science and Implications Beyond the Rotator Cuff. Issue 19 (1st October 2022) - Omid, Reza; Lalezari, Ramin; Bolia, Ioanna K.; Weber, Alexander E.
Abstract : Platelet-rich plasma (PRP) is an autologous mixture produced by centrifugal separation of whole blood. Understanding the clinical efficacy of PRP remains a challenge in the field of sports medicine, including the treatment of various shoulder conditions. Animal studies have examined the biologic actions of PRP on the rotator cuff tendon and shoulder capsule. Human studies have reported the outcomes of PRP in the management of subacromial impingement syndrome, rotator cuff tears, frozen shoulder, and glenohumeral osteoarthritis. These studies highlight the role of PRP in the nonsurgical management of these conditions and its utilization in the perioperative setting to augment tissue healing and optimize the surgical outcomes. The role of PRP as an adjunct therapy in patients undergoing rotator cuff repair has been in the spotlight during the last decade; however, a limited number of studies have examined the role of PRP in the management of non–rotator cuff shoulder conditions. This article aims to provide an overview of the biologic actions of PRP on shoulder tissues and to summarize the outcomes of PRP injection in patients with rotator cuff and non–rotator cuff disease of the shoulder. We sought to organize the existing literature and to provide recommendations on the use of PRP in various shoulder conditions, based on the existing evidence.